Candida albicans enriched in orthodontic derived white spot lesions and shaped focal supragingival bacteriome - Yang, Hao; Ma, Yansong; Xie, Xianju; Wang, Hongmei; Li, Xiaowei; Fang, Dongyu; Bai, Yuxing (Frontiers in Microbiology, 2023)
White spot lesions (WSLs) are common enamel infectious diseases in fixed orthodontic treatment, which might attribute to the dysbiosis of oral microbiome. However, the correlation of Candida albicans with oral bacteriome in WSLs still remains unrevealed. This study investigated the carriage of C. albicans and how it shaped the bacterial community in disease or healthy supragingival plaque, to explore the potential role of interkingdom interaction in orthodontic WSLs. In this study, 31 patients with WSLs (WSLs) and 23 healthy patients (Health) undergoing fixed orthodontic treatment were enrolled. The supragingival microbiota in both groups were determined using 16S rRNA gene sequencing. Colonization and abundance of C. albicans in the plaque were determined via culture-dependent and -independent methods. Among WSLs patients, the correlation of C. albicans and bacteriome was analyzed under QIIME2-based bioinformatics and Spearman’s correlation coefficient. The raw reads were deposited into the NCBI Sequence Read Archive (SRA) database (Accession Number: SRP404186). Significant differences in microbial diversity as well as composition were observed between WSLs and Health groups. Leptotrichia remarkably enriched in the WSLs group, while Neisseria and Cardiobacterium significantly enriched in the Health group. In addition, 45% of WSLs patients were C. albicans carriers but none in patients without WSLs. Among all WSLs patients, beta diversity and microbial composition were distinguished between C. albicans carriers and non-carriers. In C. albicans carriers, Corynebacterium matruchotii and Streptococcus mutans significantly enriched whereas Saccharibacteria_TM7_G-1 significantly depleted. The abundance of C. albicans was positively associated with bacteria such as Streptococcus mutans, while the negative correlation was detected between C. albicans and several bacteria such as Cardiobacterium hominis and Streptococcus sanguinis. Our study elucidated the distinguished supragingival plaque microbiome between orthodontic patients with and without WSLs. C. albicans frequently existed and enriched in orthodontic derived WSLs. The carriage of C. albicans shape plaque bacterial community in demineralized lesions and might play roles in WSLs pathogenesis.